Inclusive, prompt and non-prompt J/ψ production at midrapidity in p-Pb collisions at √sNN = 5.02 TeV - Acharya, Shreyasi; Angelov, Venelin; Arslandok, Mesut; Berdnikova, Anastasia; Bergmann, Luisa; Danisch, Meike; Feuillard, Victor; Glässel, Peter; Kim, Jiyoung; Kim, Minjung; Kroesen, Martin; Nath, Abhishek; et al. (Journal of high energy physics, 2022)
A measurement of inclusive, prompt, and non-prompt J/ψ production in p-Pb collisions at a nucleon-nucleon centre-of-mass energy sNN−−−√ = 5.02 TeV is presented. The inclusive J/ψ mesons are reconstructed in the dielectron decay channel at midrapidity down to a transverse momentum pT = 0. The inclusive J/ψ nuclear modification factor RpPb is calculated by comparing the new results in p-Pb collisions to a recently measured proton-proton reference at the same centre-of-mass energy. Non-prompt J/ψ mesons, which originate from the decay of beauty hadrons, are separated from promptly produced J/ψ on a statistical basis for pT larger than 1.0 GeV/c. These results are based on the data sample collected by the ALICE detector during the 2016 LHC p-Pb run, corresponding to an integrated luminosity Lint = 292 ± 11 μb−1, which is six times larger than the previous publications. The total uncertainty on the pT-integrated inclusive J/ψ and non-prompt J/ψ cross section are reduced by a factor 1.7 and 2.2, respectively. The measured cross sections and RpPb are compared with theoretical models that include various combinations of cold nuclear matter effects. From the non-prompt J/ψ production cross section, the bb¯¯¯ production cross section at midrapidity, dσbb¯¯¯/dy, and the total cross section extrapolated over full phase space, σbb¯¯¯, are derived.
*The ALICE Collaboration: S. Acharya, V. Anguelov, M. Arslandok, A. Berdnikova, L. Bergmann, M.C. Danisch, V.J.G. Feulliard, P. Glaessel, J. Kim, M. Kim, M. Kroesen, A. Nath, Y. Pachmayer, K. Reygers, R. Schicker, A. Schmah, M.O. Schmidt, G. Skorodumovs, J. Stachel, S.F. Stiefelmaier, M.A. Völkl, B. Windelband, A. Yuncu [und sehr viele weitere Personen]
Gesehen am 22.07.2022
Im Titel steht der Ausdruck "sNN" unter dem Wurzelsymbol